Uterine venous malformations in the puerperium: 2 Atypical cases and literature review - Gianluca Raffaello Damiani; Miriam Dellino; Eliano Cascardi; He Xuamin; Daniele Di Gennaro; Antonella Vimercati; Amerigo Vitagliano; Antonio Malvasi; Vera loizzi; Cristiana Paniga; Laura Lanteri; Raffaello Alfonso; et al. (Elsevier, 2023)
Uterine arteriovenous malformations (AVMs) is a rare but high-risk cause of uterine bleeding. The clinical management of this condition is challenging, as the ultrasound picture can sometimes be unambiguously interpreted. Moreover, in the puerperium in which acquired AVMs are most frequently formed, it is necessary to discuss the correct management in a multidisciplinary and personalized manner. We present two cases of AVMs developing in the puerperium, both with a vaginal delivery and spontaneous and complete secondment. The symptom of onset was an episode of bright red blood loss in the puerperium, on the 14th and 21st postpartum days, respectively. Transvaginal ultrasound showed a hypervascularized lesion in the myometrium with turbulent vascular flow, confirmed by transabdominal ultrasound and angiography. To date, there are no guidelines on the management of MAVs. In our cases we opted for a conservative approach, in order to preserve the fertility of the patient. These experiences reported have the purpose of enriching a literature still sparse on the subject and in the future to be able to represent a fulcrum for official recommendations.